A young male with epitheliolysis in the small bowel and colon. (3rd May 2020) - Kvarme, Heidi; Fjellanger, Renée; Bondevik, Camilla; Astor, Marianne Catharina; Barrett, Torill; Haugen, Oddbjørn; Storebråten, Gøril; Karliczek, Anne; Vaagbø, Guro; Sande Leikanger, Ingrid; Tveit, Kåre Steinar; Engjom, Trond; et al.
Abstract: Background: Toxic epidermal necrolysis (TEN) is characterized by epidermal necrosis of various degree, and can affect the entire body surface. Affection of small bowel and colon is a rare manifestation of TEN. We present a case with an unusual appearance of epitheliolysis of the small bowel and colon due to a toxic reaction. Case report: A 19 year old male was diagnosed with ulcerative colitis (UC) after treatment with tetracyclines followed by isotretinoin due to acne vulgaris. Medical treatment did not lead to improvement of his UC, and an emergency resection of the colon was performed. Postoperatively his condition worsened due to small bowel epitheliolysis, and he recovered finally 6 months later after a partial small bowel resection. Conclusion: The true cause of this very serious situation with severe gastrointestinal involvement is not fully understood. In this case, successive treatment with antibiotics and isotretinoin given to a patient with an inflamed colon might have triggered the destruction of the epithelial barrier, leading to an immense immunological reaction in the intestinal wall. We suggest that physicians should be aware of UC-like symptoms occurring prior to or during treatment with tetracyclines and/or isotretinoin.